Artificial Intelligence (AI) Technology Trends in Human Resource Productivity: A Bibliometric and Content Analysis - Zahril Maulana Jilham Al'ula; Astra Savero Qomara; Tyassatrio Kuncorowibowo; Syarifa Hanoum (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2024)
Purpose – This research aims to show research trends in the field of AI implementation in the human resources realm and its relationship with human resource productivity Methodology – This research combines bibliometric analysis with content analysis methods. Bibliometric analysis is carried out by quantitative and statistical analysis of a set of data that is linked using bibliometric indicators that represent a set of topics that are the research area in this study. Then the findings from the bibliometric method are supported by content analysis from various studies in this research area, so that it can produce output with a clearer perspective. Findings – This research show that Artificial Intelligence (AI) can have significant effect on productivity in some case, but it must also be acknowledged that companies must also be wise in ensuring that the work to be adapted with the help of AI is appropriate, because the implementation of AI has not yet reached the point where all human work can be assisted or replaced by AI. Research Limitation – This research was conducted only through the findings on several previous research, articles, and the data obtained from Scopus only. Practical Implications – Based on the bibliometric analysis of recent trends in AI technology and its impact on human resource productivity, it is recommended that organizations invest in AI-based HR tools and systems to improve their productivity and efficiency. The study highlights the need for HR professionals to stay up to date with the latest AI trends and technologies to remain competitive in the job market.